Prevalence and risk factors associated with depressive symptoms among end-stage renal disease patients undergoing hemodialysis in Indian setting - Bhatia, Rajeev Kumar; Marwaha, Ajay (International Journal of Research in Medical Sciences, 2020)
Background: This study aimed to evaluate the prevalence of depressive symptoms among the patients with end-stage renal disease (ESRD) on hemodialysis and to explore associated risk factors. Methods: A prospective observational study of patients with ESRD undergoing hemodialysis were included in the study. Data was collected based on questionnaire created by the study team, and by verbal interviews with patients. The questionnaire consisted of two parts, which included demographic data (gender, age, sleep quality, duration of sleep, appetite pattern, and duration of dialysis) and evaluation of the severity of depressive symptoms by using the depression, anxiety and stress scale-21. Results: Out of total 93 patients with ESRD on hemodialysis majority of patients belonged to the age group of >60 to ≤80 years (47.8%) and age group >40 to ≤60 years (40.0%). Patients had a higher incidence of severe anxiety (38.7%) than depression (34.4%), and stress (22.6%). The proportion of patients diagnosed with depression (50.0%) and stress (57.1%) was higher in the older age group (>60 to ≤80 years); while the proportion of patients having severe anxiety was similar in both adult (>40 to ≤60 years) and older (>60 to ≤80 years) age group (38.9%). More than 50% of patients with depressive, anxiety, and stress symptoms had insufficient sleep (≤1 to ≤4 h). The present study could not predict the risk factors of depressive symptoms in patients with ESRD on hemodialysis. Conclusions: Depression and anxiety symptoms were more frequent among patients with ESRD undergoing hemodialysis in Indian settings.